THE ROLE OF VOCABULARY BASE IN READING - * (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Reading comprehension is an important skill for navigating the textual world around us. It is a dynamic process that involves making predictions, summarizing the main idea, questioning one’s predictions, and clarifying unclear concepts. This paper will gives emphasis on to what extent vocabulary base has significance in reading comprehension and mostly, to boost reading score.